2016
DOI: 10.1161/jaha.116.003575
|View full text |Cite
|
Sign up to set email alerts
|

25‐Hydroxyvitamin D Levels and Markers of Subclinical Myocardial Damage and Wall Stress: The Atherosclerosis Risk in Communities Study

Abstract: BackgroundLow 25‐hydroxyvitamin D (25[OH]D) is associated with increased cardiovascular disease risk. Less known is whether 25(OH)D deficiency contributes to subclinical myocardial damage and wall stress (high‐sensitivity cardiac troponin T [hs‐cTnT] and N‐terminal pro–brain natriuretic peptide [NT‐proBNP]) or whether associations vary among subgroups.Methods and ResultsOverall, 11 311 Atherosclerosis Risk in Communities participants without prevalent cardiovascular disease had 25(OH)D, hs‐cTnT, and NT‐proBNP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…An inverse correlation between the vitamin D level and the stage of coronary atherosclerosis along with the levels of total cholesterol, LDL and triglycerides in women and men over 70 years has been reported [100]. Similarly, low levels of vitamin D have been associated with subclinical atherosclerosis, increased expression of high-sensitivity cardiac troponin T and N-terminal pro–brain natriuretic peptide (markers of subclinical myocardial damage and wall stress) [101]. In addition, the role of vitamin D binding protein (VDBP) and its polymorphism in relation to atherosclerosis and the role of VDBP in resistance to atherosclerosis leading to the longevity of patients have also been examined [102].…”
Section: Vascular Diseasementioning
confidence: 99%
“…An inverse correlation between the vitamin D level and the stage of coronary atherosclerosis along with the levels of total cholesterol, LDL and triglycerides in women and men over 70 years has been reported [100]. Similarly, low levels of vitamin D have been associated with subclinical atherosclerosis, increased expression of high-sensitivity cardiac troponin T and N-terminal pro–brain natriuretic peptide (markers of subclinical myocardial damage and wall stress) [101]. In addition, the role of vitamin D binding protein (VDBP) and its polymorphism in relation to atherosclerosis and the role of VDBP in resistance to atherosclerosis leading to the longevity of patients have also been examined [102].…”
Section: Vascular Diseasementioning
confidence: 99%
“…The inverse correlation between cTnT and VIT-D 3 blood levels was reported in many clinical studies, where low VIT-D 3 levels were associated with raised CTnT levels (Hur et al, 2009;Michos et al, 2016). Likewise, a recent study showed that supplementation of VIT-D 3 significantly reduced cTnT in breast cancer treatment with adjuvant DX chemotherapy (El-Bassiouny et al, 2022).…”
Section: Scintigraphic Assaymentioning
confidence: 84%
“…Methods for ascertaining participant characteristics and laboratory measures in ARIC have previously been described 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 and are detailed in Data S1 . All laboratory measures were performed at visit 5.…”
Section: Methodsmentioning
confidence: 99%